Proceedings of the 19th International Symposium on Automation and Robotics in Construction (ISARC) 2002
DOI: 10.22260/isarc2002/0032
|View full text |Cite
|
Sign up to set email alerts
|

A Tool to Improve Efficiency in Large Scale Manufacturing

Abstract: ABSTRACT:NIST is working directly with industry to improve repair and conversion operations of ships in dry dock. This work allows transfer of technology to construction and other industries requiring worker-access to large, external surfaces with minimum footprint and maximum system rigidity and control, while augmenting conventional suspended-scaffold systems and moving toward more autonomous large-scale manufacturing applications such as building construction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…CDPR-related research has been reported since 1984, originally for underwater applications. The RoboCrane project [25], developed under the Defense Advanced Research Project Agency (DARPA), extended CDPR applications to land, sea, air, and space. CDPRs show high load-to-weight ratio, while relying on stable configurations, flexibility, and maneuverability over rough terrain surfaces.…”
Section: Mobile Cdprsmentioning
confidence: 99%
“…CDPR-related research has been reported since 1984, originally for underwater applications. The RoboCrane project [25], developed under the Defense Advanced Research Project Agency (DARPA), extended CDPR applications to land, sea, air, and space. CDPRs show high load-to-weight ratio, while relying on stable configurations, flexibility, and maneuverability over rough terrain surfaces.…”
Section: Mobile Cdprsmentioning
confidence: 99%
“…The moveable platform, or "lower triangle," is kinematically constrained by maintaining tension in six cables that terminate in pairs at the vertices of an "upper triangle" formed by the cable support points [5]. The RoboCrane concept has been modified and adapted for numerous specialized applications [6,7,8]. The configuration used in this project is the Tetrahedral Robotic Apparatus (TETRA).…”
Section: Nist Robocranementioning
confidence: 99%
“…One of the first CDPR was Robocrane is shown in Figure 1, which was developed in 1989 in the USA by the National Institute of Standards and Technology (NIST). 1,2 CDPR Robocrane was intended for handling cargo in ports, during the construction of bridges, and so on. CDPR Robocrane is a Gough-Stuart platform suspended on six cables.…”
Section: Introductionmentioning
confidence: 99%
“…If in a CDPR all drive cables are above the EE, and gravity acts as a virtual cable to maintain balance, then such the EE is called suspended. 1,6 8 If in the CDPR at least one drive cable is below the EE, then such a CDPR is called not suspended. 9,10…”
Section: Introductionmentioning
confidence: 99%